Assembly and transfer of tripartite integrative and conjugative genetic elements - Haskett, T.; Terpolilli, J.; Bekuma, A.; O'Hara, G.; Sullivan, J.; Wang, P.; Ronson, C.; Ramsay, Joshua (National Academy of Sciences, 2016)
Integrative and conjugative elements (ICEs) are ubiquitous mobile genetic elements present as "genomic islands" within bacterial chromosomes. Symbiosis islands are ICEs that convert nonsymbiotic mesorhizobia into symbionts of legumes. Here we report the discovery of symbiosis ICEs that exist as three separate chromosomal regions when integrated in their hosts, but through recombination assemble as a single circular ICE for conjugative transfer. Whole-genome comparisons revealed exconjugants derived from nonsymbiotic mesorhizobia received three separate chromosomal regions from the donor Mesorhizobium ciceri WSM1271. The three regions were each bordered by two nonhomologous integrase attachment (att) sites, which together comprised three homologous pairs of attL and attR sites. Sequential recombination between each attL and attR pair produced corresponding attP and attB sites and joined the three fragments to produce a single circular ICE, ICEMcSym1271. A plasmid carrying the three attP sites was used to recreate the process of tripartite ICE integration and to confirm the role of integrase genes intS, intM, and intG in this process. Nine additional tripartite ICEs were identified in diverse mesorhizobia and transfer was demonstrated for three of them. The transfer of tripartite ICEs to nonsymbiotic mesorhizobia explains the evolution of competitive but suboptimal N2-fixing strains found in Western Australian soils. The unheralded existence of tripartite ICEs raises the possibility that multipartite elements reside in other organisms, but have been overlooked because of their unusual biology. These discoveries reveal mechanisms by which integrases dramatically manipulate bacterial genomes to allow cotransfer of disparate chromosomal regions.